Performance measures and security risk management: a Hong Kong example - Brewer, Brian; Huque, Ahmed Shafiqul (2004)
Public agencies have an important role in establishing and ensuring a secure environment for business operations. Risk management decisions by international business enterprises can be informed usefully by performance data related to the services provided by a host country's law enforcement agencies. As recent public sector reforms have emphasized the development of indicators and the measurement of performance in public organizations, such as the police, this has made it possible for businesses to use these data to enhance the quality of their decisions about security needs related to both personnel and property. This article reviews the number of emergency calls received by the Hong Kong police and their response time and examines what inferences can be drawn from these data. Such an analysis highlights the need to compare the contrast different performance measures to obtain a comprehensive view of an agency's performance before making critical business decisions. - Reproduced.
Keywords: Disaster prevention - Hong Kong; Performance appraisal - Hong Kong; Performance appraisal